Kombucha bacterial cellulose for sustainable fashion. Issue 5 (2nd September 2019) - Domskiene, Jurgita; Sederaviciute, Florentina; Simonaityte, Judita
Abstract : Purpose: The purpose of this paper is to analyse the properties of bacterial cellulose (BC) film, obtained through Kombucha tea fermentation. Design/methodology/approach: Kombucha fungus was used to produce BC film under static cultivation conditions. Physical and mechanical properties under the influence of drying temperature and durability of BC material were investigated. Tensile properties were estimated by TINIUS OLSEN H10 KT test machine according to ISO 3376:2011, thickness was measured by DPT 60. BC structure was analysed by Scanning Electron Microscopy Quanta 200 FEG. Findings: BC material with excellent deformation properties in wet state were obtained by fermenting Kombucha tea. Due to the presence of fermentation residues, Kombucha film is sensitive to drying temperature. The best deformation properties retain when BC material is dried at low temperature (about 25°C). BC material becomes stiffer and ruptures at lower deformations due to rapid water evaporation at higher drying temperature. It is confirmed that during time, the properties of BC film changes significantly and there may be problems with the durability of products from this material. BC film has an interesting set of properties, therefore its application to fashion industry without further preparation is limited. Originality/value: A new approach is based on the evaluation of Kombucha material properties and investigation of BC as new type of material for fashion industry. Some recommendations for Kombucha BC film production are provided, basing on gained experience, experimental results and analysed literature. The advantages and disadvantages of material are discussed in the paper, in order to search for the ways to adapt the new type of material to fashion business.